Expression analysis of Toll like receptors and interleukins in Tharparkar cattle during acclimation to heat stress exposure. (April 2017) - Bharati, Jaya; Dangi, S.S.; Mishra, S.R.; Chouhan, V.S.; Verma, V.; Shankar, O.; Bharti, M.K.; Paul, A.; Mahato, Dilip K.; Rajesh, G.; Singh, G.; Maurya, V.P.; et al.
Abstract: Six male Tharparkar cattle of 2–3 years old were selected for the study. After 15 days acclimation at thermo neutral zone (TNZ) in psychrometric chamber, animals were exposed at 42 °C for 6 h up to 23 days followed by 12 days of recovery period. Blood samples were collected during control period at TNZ (day 1, 5 and 12), after heat stress exposure (day 1–10, Short Term Heat Stress Acclimation- STHSA; day 15–23, Long Term Heat Stress Acclimation- LTHSA) and recovery period (day 7 and 12) and peripheral blood mononuclear cells (PBMCs) were isolated for RNA and protein extraction. Serum cortisol concentration was assessed by RIA. The mRNA and protein expression in PBMCs were determined by qPCR and western blot respectively. Samples at TNZ were taken as control. Serum cortisol concentration was increased (P<0.05) during STHSA and gradually declined during LTHSA. Toll like receptor 2 (TLR 2) expression was up regulated (P<0.05) during STHSA and declined to basal level during LTHSA and recovery phase. However, toll like receptor 4 (TLR 4) expression was up regulated (P<0.05) during STHSA and LTHSA while declined in recovery phase. Interleukin 2 (IL2) and interleukin 6 (IL 6) were up regulated (P<0.05) during STHSA and reduced to basal level during LTHSA. PBMCs culture study was conducted to study transcriptional abundance of TLR2/4 and IL2/6 at different temperature-time combinations. The present findings indicate that TLR 2/4 and IL 2/6 could possibly play a vital role in thermo tolerance in Tharparkar cattle during short term and long term heat stress exposure. Highlights: Expression of TLRs and interleukins were studied during heat exposure in cattle. Expression of TLR2/4 and IL2/6 was modified during heat exposure. This indicate TLR 2/4 and IL 2/6 play a vital role in thermo tolerance in cattle.